Determination of the incidence of embryonic death by means of real-time ultrasound scanning in ewes - M. Kemal SARIBAY; Hüseyin ERDEM (Eurasian Journal of Veterinary Sciences)
In the present study, incidence of embryonic mortality in ewes was determined directly by real-time ultrasonography and indirectly by changes in level of plasma progesterone. Then the results were evaluated. Multiparous Konya Merino ewes (n=60), which were housed under the same conditions, were flushed and naturally mated between September 17 and October 7. The first pregnancy detection was done transrectally 18 days after mating by using linear array probe, 5 MHz real-time ultrasonography. Ewes, which were confirmed pregnant on day 18, were repeatedly examined by ultrasonography for pregnancy 22, 26, 30, and 34 days after mating. Blood samples were collected simultaenously with ultrasonography and measurements of plasma progesterone with enzyme immunoassay (EIA). Of 73 ewes, 60 ewes were pregnant and 79 embryos were detected and embryonic mortality rate was 8.9 % (7 of 79 embriyos) on day 18. Of these embryonic mortalities, 2 on day 22, 4 on day 26 and 1 on day 34 happened. As a result, there is noticeable significant embryonic loss in late embryonic period. Measurements of plasma progesterone levels are not sufficient to determine embryonic mortality. However, ultrasonography is a dependable method to determine the time and the incidence of the embryonic death.